[OP.6B.03] KIF1B AND NF1 ARE THE MOST FREQUENTLY MUTATED GENES IN PARAGANGLIOMAS AND PHEOCHROMOCYTOMAS TUMOURS FROM A BELGIAN MULTICENTRIC COHORT. (September 2017) - Evenepoel, L.; Helaers, R.; Vroonen, L.; Aydin, S.; Hamoir, M.; Maiter, D.; Vikkula, M.; Persu, A.
Abstract : Objective: Pheochromocytomas/paragangliomas (PPGLs) are rare chromaffin-cell tumours arising from the adrenal medulla or extra-adrenal paraganglia, respectively. Forty percent of PPGLs are explained by germline mutations in known susceptibility genes. Recently, somatic point mutations were identified in an additional 30% of PPGLs, using Sanger sequencing, mainly in the NF1, VHL, RET, and HRAS genes. However, recently identified susceptibility genes, such as FH and KIF1B, were not screened. Our aim was to look for the prevalence and nature of somatic mutations in patients from a Belgian multicentric PPGL cohort using targeted deep-sequencing. Design and method: Targeted Next Generation Sequencing was performed using the Ion Torrent system (Life Technologies®) with a panel including 17 susceptibility genes. Variants predicted as damaging by at least 5 programs, or present in COSMIC and predicted by at least 3 programs were considered to be mutations. Results: Tumours and their corresponding blood samples were available for 74 PPGL patients (age at diagnosis: 45.4 ± 16.2 years; females: 55%; head and neck paragangliomas: 31%). Somatic mutations were identified in 40 patients (54%), 6 of which had a germline mutation (5 SDHD and 1 SDHB). The average number of mutations per patient was 7.9 ± 19.4 (range: 1–119). Mutations were more frequent in genes involved in Cluster 2 than in Cluster 1 (58% vs 42%, p-value = 0.003). The most frequently mutated genes were: NF1 (20.8%), KIF1B (20.4%) and RET (11%). Notably, RET mutations were more frequent in paragangliomas than in pheochromocytomas (20% vs. 5%, p < 0, 008). Conclusions: Somatic mutations were found in 54% of patients. The high prevalence of somatic mutations in NF1 is in agreement with previous studies, while the similarly elevated prevalence of mutations in KIF1B is a novel finding. The second main result is the high proportion of RET somatic mutations in head and neck paragangliomas compared to pheochromocytomas. Finally, we identified a minority of tumours with a large number of somatic mutations, which may reflect perturbations in DNA damage repair. Whether such tumours are more prone to dissemination and recurrence remains to be demonstrated.